(untitled) (Revista Brasileira de Contabilidade e Gestão, 2021)
Given the current economic scenario, organizations must pay attention to strategic planning aimed at reducing business expenses. This article addresses the use of Zero Base Budget (OBZ) with the aim of analyzing the implementation of the method in an AMBEV beverage distributor. As for the methodology, it is a qualitative study, classifying itself as an exploratory research where technical procedures of bibliographic, documental and case study analysis were used. The results presented show that the implementation of the OBZ method is a complex and time-consuming process, but it brings benefits to the company, as it promotes improvements in information to management and in the alignment between teams in the allocation of resources efficiently, facilitating managers in their decision-making. It is understood that this research contributes to academia by presenting the methodology for implementing the OBZ in an AMBEV dealership, being a mandatory management requirement for the company’s dealers. Finally, the study suggests for future research the comparison between expectations with the implementation of the budget and the reality after the results at the end of the year, comparing one period with another.